2021
DOI: 10.1088/1361-6528/ac37e4
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion, MRI imaging and optical trapping studies of silver nanoparticle decorated multifunctional NaGdF4:Yb,Er nanocomposite

Abstract: The multifunctional upconversion nanoparticles (UCNPs) are fascinating tool for biological applications. In the present work, photon upconverting NaGdF4:Yb,Er and Ag nanoparticles decorated NaGdF4:Yb,Er (NaGdF4:Yb,Er@Ag) nanoparticles were prepared using a simple polyol process. Rietveld refinement was performed for detailed crystal structural and phase fraction analysis. The morphology of the NaGdF4:Yb,Er@Ag was examined using high-resolution transmission electron microscope, which reveals silver nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Therefore, we found that phagocytic cells (such as monocytes and dendritic cells) had higher affinity to the UCNPs than the other nonphagocytic cells. In addition, PG clustering algorithms were used to identify sub-cell types of monocytes and dendritic cells, which is sub-divided into 3 clusters (PG#1, 4, 18) and 4 clusters (PG#2, 3,19,27), respectively. Our study demonstrated a new technical framework to understand the heterogeneous interactions of conventional nanomaterials with complex human immune cells, which will be helpful for the safe use of nanomaterials in biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we found that phagocytic cells (such as monocytes and dendritic cells) had higher affinity to the UCNPs than the other nonphagocytic cells. In addition, PG clustering algorithms were used to identify sub-cell types of monocytes and dendritic cells, which is sub-divided into 3 clusters (PG#1, 4, 18) and 4 clusters (PG#2, 3,19,27), respectively. Our study demonstrated a new technical framework to understand the heterogeneous interactions of conventional nanomaterials with complex human immune cells, which will be helpful for the safe use of nanomaterials in biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, lanthanide-doped upconversion nanoparticles (UCNPs) convert low-energy light into higherenergy light by multiphoton absorption, which is advantageous to increasing the penetration depth and reducing autofluorescence and photobleaching under a nearinfrared (NIR) laser. 17,18 The unique optical properties of UCNPs make them the best candidates for effective biomedical applications, such as MRI, 19 chemical sensing, 4 drug delivery, 20 color display technologies, 21 solar cells, 22 and photoswitching. 23 With the increasing application of UCNPs, there are increasing concerns about the possible toxicity of UCNPs to human health.…”
Section: Introductionmentioning
confidence: 99%
“…The core of NaGdF 4 :Yb/Er was synthesized by a thermal decomposition method [ 35 ]. Briefly, a 50-ml 3-necked flask containing 15 ml of OA and 30 ml of ODE was added with 0.25 mmol of Yb(CH 3 CO 2 ) 3 , 0.745 mmol of Gd(CH 3 CO 2 ) 3 , and 0.005 mmol of Er(CH 3 CO 2 ) 3 , heated at 160 °C to make a clear solution, and then cooled to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[86] Gadolinium particles can also be used in trimodal CT/ MRI/UCL imaging. [228] One potential drawback in MRI-UCNP bimodal imaging could be the extent of nanoparticle delivery efficiency, as most in vitro UCNP-MRI experiments showed limits of UCNP detection when gadolinium concentrations were in the single μM range. [225,229] Additionally, research into erbium-based UCNPs showed a reduction in UCL intensity with gadolinium instead of yttrium particle cores, potentially hindering UCL/MR multimodal imaging.…”
Section: Applications Of Ucnps In Multimodal Bioimagingmentioning
confidence: 99%